2016
DOI: 10.5812/aapm.11519
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Hemodynamic Effects of Spinal Anesthesia in Preeclamptic and Healthy Parturients During Cesarean Section

Abstract: BackgroundDespite controversies about the safest anesthetic technique for cesarean delivery in severely preeclamptic women, there is evidence that supports the use of spinal anesthesia in this group of patients.ObjectivesThis prospective randomized clinical trial was designed to determine the hemodynamic effects of low-dose spinal bupivacaine and the incidence of spinal anesthesia-associated hypotension in severely preeclamptic and healthy parturients undergoing cesarean sections.Patients and MethodsSpinal ane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 26 publications
4
24
1
Order By: Relevance
“…[27][28][29] The same has been observed in other high-risk patients, such as women in labour. 30 The mechanism underlying fetal acidosis associated with ephedrine has been postulated to be associated with placental transfer and stimulation of fetal metabolism. 31 Use of smaller doses of vasopressors in high-risk patients would reduce any adverse effects of placental drug transfer.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29] The same has been observed in other high-risk patients, such as women in labour. 30 The mechanism underlying fetal acidosis associated with ephedrine has been postulated to be associated with placental transfer and stimulation of fetal metabolism. 31 Use of smaller doses of vasopressors in high-risk patients would reduce any adverse effects of placental drug transfer.…”
Section: Discussionmentioning
confidence: 99%
“…Preeclampsia-induced endothelial dysfunction leads to increases in endothelin and thromboxane production, decreased vasodilator synthesis, and sensitizes the vasculature to vasoconstrictors (39). Previous studies indicated that spinal anesthesia-induced hypotension was less frequent and less severe in preeclamptic patients when compared to normotensive parturients, and minimal doses of vasopressors are typically required to restore maternal blood pressure to baseline (35, 36, 40) (Table 2). Similarly, Ituk et al recently conducted a retrospective comparison of phenylephrine and ephedrine for management of spinal-induced hypotension in preeclamptic patients and observed that approximately 50% of patients did not experience hypotension requiring vasopressor treatment following spinal anesthesia (37).…”
Section: Resultsmentioning
confidence: 99%
“…Preeclampsia: A pregnancy-induced increase in blood pressure ≥ 140/90 mmHg after 20 weeks of gestation and proteinuria ≥ 300 mg/24 hrs [10]. Preeclampsia with severity feature/severe preeclampsia: Defined as a systolic arterial blood pressure of 160 mmHg or higher, or a diastolic blood pressure of 110 mmHg or higher, associated with proteinuria > 5 g in 24 hours [10,35]. Change in heart rate: When there was a 20% decrease or increase in heart rate from baseline [6,10,25,26,36].…”
Section: Methodsmentioning
confidence: 99%
“…But these preemptive measures could put the preeclamptic patients at increased risk of hypertension and pulmonary edema [9]. Due to inconsistent definition, the reported incidence of spinal anesthesia-induced maternal hypotension varies between 7% and 89.2% [10,16]. Therefore, anesthetic management for preeclamptic parturients who undergo cesarean section is challenging for anesthetists [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation